Interactive alignment as an allostatic process: A literature review (2024)
Research on interactive alignment encompasses various perspectives, including the recognition of linguistic coordination patterns, mental representation processes between interlocutors, and linguistic and behavioral convergence. In the absence of a literature review that presents the advances in the study of interactive alignment, this study identified 64 theoretical and empirical articles developed over 25 years (1996–2021) following the PRISMA methodology. Methodological and theoretical aspects derived from the analysis of the aforementioned reports are presented, showing how synchronization parameters interact, the associated neural bases, the impact of alignment on the development of joint actions, cognitive load, social interactions in general, and the prediction of language. The discussion and conclusions analyze the information presented and propose a comprehensive analysis from an allostatic perspective (predictive regulation through change) to advance the understanding of interactive alignment.